2021
DOI: 10.1093/gbe/evab093
|View full text |Cite
|
Sign up to set email alerts
|

Gene Coexpression Network Reveals Highly Conserved, Well-Regulated Anti-Ageing Mechanisms in Old Ant Queens

Abstract: Evolutionary theories of ageing predict a reduction in selection efficiency with age, a so-called ‘selection shadow’, due to extrinsic mortality decreasing effective population size with age. Classic symptoms of ageing include a deterioration in transcriptional regulation and protein homeostasis. Understanding how ant queens defy the trade-off between fecundity and lifespan remains a major challenge for the evolutionary theory of ageing. It has often been discussed that the low extrinsic mortality of ant queen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 83 publications
3
7
0
Order By: Relevance
“…We predict that the evolution of a constant or decreasing mortality curve, or longevity, should lead to increasing purifying selection on late-expressed genes, which should be measurable using standard transcriptome experiments. This has been exactly what Harrison and colleagues have observed: higher protein sequence conservation among old-biased genes in ant queens (Harrison et al, 2021). However, it remains possible that age-related changes in cell type composition (e.g.…”
Section: Discussionsupporting
confidence: 71%
“…We predict that the evolution of a constant or decreasing mortality curve, or longevity, should lead to increasing purifying selection on late-expressed genes, which should be measurable using standard transcriptome experiments. This has been exactly what Harrison and colleagues have observed: higher protein sequence conservation among old-biased genes in ant queens (Harrison et al, 2021). However, it remains possible that age-related changes in cell type composition (e.g.…”
Section: Discussionsupporting
confidence: 71%
“…Strikingly, a comparative transcriptomic study of 8-week young queens with fully mature C. obscurior queens at or close to their peak fecundity (18 weeks old) did not find signs indicative of aging, but in comparison to aged Drosophila flies an opposite regulation of processes (e.g., cellular ketone, carbohydrate, and organic acid metabolic processes) and genes (e.g., ref(2)P , emp , P5cr-2 , CCHa2 , NLaz , Sirt6 ) involved in aging ( von Wyschetzki et al, 2015 ). Furthermore, a gene co-expression network study using the same data showed higher connectivity in middle-aged queens, indicating increased transcriptional regulation with age ( Harrison et al, 2021 ). Together, this suggests that the physiology of queens is maintained until the fitness peak is reached, at which time they undergo physiological deterioration, while still being reproductively active.…”
Section: Discussionmentioning
confidence: 96%
“…In M. natalensis , for instance, which is the focus of the current study, sterile workers live only weeks, while kings and queens can live for over 20 years [ 17 ], with the highly fertile queen laying thousands of eggs per day [ 18 ]. Several important genes and pathways have been indicated as important for longevity and fecundity in termites and other eusocial insects, such as the nutrient-sensing pathways Insulin/insulin-like growth factor (IGF-1) signalling (IIS) and target of rapamycin (TOR) [ 16 , 19 , 20 ], telomerase [ 21 ], transposon defence [ 16 , 22 ], oxidative stress [ 16 , 20 , 23 ], DNA damage repair and mitochondrial functions [ 20 , 23 ] Further, recent studies have also presented evidence for the transcriptional regulation of specific gene co-expression modules associated with old but highly fertile queens in ants [ 24 ], bees [ 25 ] and termites [ 20 , 26 , 27 ]. However, the role of DNA methylation in this absence of the longevity–fecundity trade-off in eusocial insects is so far unknown.…”
Section: Introductionmentioning
confidence: 99%